2015
DOI: 10.1111/tan.12671
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 and CD28 genes' polymorphisms and renal cell carcinoma susceptibility in the Polish population – a prospective study

Abstract: Polymorphisms in co-stimulatory genes are associated with susceptibility to several malignances such as breast cancer, cervical cancer and chronic lymphocytic leukemia, but have been scarcely investigated in renal cell cancer (RCC). A total of 310 RCC patients and 518 controls were genotyped for single-nucleotide polymorphisms (SNPs) in the CTLA-4 and CD28 genes: CTLA-4c.49A>G (rs231775), CTLA-4g.319C>T (rs5742909), CTLA-4g.*6230G>A (CT60; rs3087243), CTLA-4g.*10223G>T (Jo31; rs11571302), CD28c.17+3T>C (rs3116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Moreover, there were 30 studies with 9675 cases and 9623 controls for rs3087243 [12-15, 17, 23-25, 27-29, 31, 32, 35, 37, 40, 41, 44, 45, 47, 53, 54, 61, 63, 65, 66, 73-75]. Additionally, rs4553808 was in 17 studies [12, 14, 15, 23, 28, 29, 31, 37, 41, 44, 47, 49, 51, 52, 62, 73, 76], rs5742909 was in 32 studies [12, 14, 15, 20, 24, 25, 28-30, 32, 34, 35, 39-41, 45, 47, 52-54, 56, 57, 59, 62, 63, 65, 66, 70, 73, 76, 77], rs733618 was in 14 studies [13, 23, 28, 37, 44, 47, 51, 52, 62, 73-76, 78], and they were analysed. Of the 67 studies, 9 presented a significant deviation from HWE (5 studies on rs231775 [11, 13, 34, 51, 66], 4 studies on rs4553808 [51, 62…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there were 30 studies with 9675 cases and 9623 controls for rs3087243 [12-15, 17, 23-25, 27-29, 31, 32, 35, 37, 40, 41, 44, 45, 47, 53, 54, 61, 63, 65, 66, 73-75]. Additionally, rs4553808 was in 17 studies [12, 14, 15, 23, 28, 29, 31, 37, 41, 44, 47, 49, 51, 52, 62, 73, 76], rs5742909 was in 32 studies [12, 14, 15, 20, 24, 25, 28-30, 32, 34, 35, 39-41, 45, 47, 52-54, 56, 57, 59, 62, 63, 65, 66, 70, 73, 76, 77], rs733618 was in 14 studies [13, 23, 28, 37, 44, 47, 51, 52, 62, 73-76, 78], and they were analysed. Of the 67 studies, 9 presented a significant deviation from HWE (5 studies on rs231775 [11, 13, 34, 51, 66], 4 studies on rs4553808 [51, 62…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested thatSNPs [+49 (rs231775), CT60 (rs3087243), −1661 (rs4553808), and −318 (rs5742909)] in the promoter region of CTLA-4 gene may modulate the gene expression and are associated with susceptibility to different types of malignances, such as colorectal cancer [45,46], breast cancer [43], hepatocellular carcinoma [47,48], cervical cancer [48][49][50], melanoma [51], head and neck cancer [52], NSCLC [53,54], renal cell carcinoma [55]and others [56] (Fig. 1B).…”
Section: Ctla-4 Polymorphisms In Cancermentioning
confidence: 99%
“…Interestingly, the association of the both SNPs with another urinary cancer -clear cell renal cell cancer was found by our group [55]. An increasing number of studies have been devoted to the association between the CT60 and Jo31 SNPs and cancers.…”
Section: Discussionmentioning
confidence: 92%